2018
DOI: 10.5851/kosfa.2018.e41
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hen Aging on Eggshell Ultrastructure and Shell Mineral Components

Abstract: The eggshell, which is a complex and highly ordered structure, is very important factor for food safety and egg marketing. This study investigated the changes in eggshell structure and shell components in relationship to hen age. For this study, we examined the histological change of the endometrium of the 30-, 60-, and 72-wk-old commercial layers, and analyzed the ultrastructure and ionic composition of their eggshells. The results showed that histological deformation, fibrosis, atrophy and elimination of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 45 publications
4
59
1
1
Order By: Relevance
“…The overlap between the genes for both time points (see Figure 2) reflects that certain molecular functions remain relevant to eggshell development during the laying cycle of chicken. Particularly, the similarity of genes responsible for the transportation of ions is in line with the findings of Park et al [100] and Fan et al [51] who found that the concentration level of different ions in blood does not change with the age of chicken. Interestingly, a closer look at the biological processes of these traits reveals that, while highly significant GO terms are involved in development for ESS1, the significant biological processes for ESS2 are rather related to different metabolic processes (Table S3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overlap between the genes for both time points (see Figure 2) reflects that certain molecular functions remain relevant to eggshell development during the laying cycle of chicken. Particularly, the similarity of genes responsible for the transportation of ions is in line with the findings of Park et al [100] and Fan et al [51] who found that the concentration level of different ions in blood does not change with the age of chicken. Interestingly, a closer look at the biological processes of these traits reveals that, while highly significant GO terms are involved in development for ESS1, the significant biological processes for ESS2 are rather related to different metabolic processes (Table S3).…”
Section: Discussionsupporting
confidence: 86%
“…The uterine epithelium and bone are the tissues that actively take part in the development of eggshell, hence the renewal of the cells of both tissues is crucial for the synthesis of a strong eggshell [4]. Furthermore, multiple studies suggest that a declining ability of uterine epithelium cells to transport calcium is the main reason of the age-related deterioration of eggshells [51,100]. In particular, the ESS2 specific p73alpha -/ NF-Y pathway that results in the inactivation of the NF-Y transcription factor by p73 proteins and consequently causes replicative senescence of cells [90] may also point towards the underlying reason for weaker eggshells during the later stages of the production cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in the expression of matrix proteins (ovalbumin, ovotransferrin and ovocleidin-17) in uterus of laying hens were suggested by their varying concentration in eggshell [20,21]. Besides, a destructed uterine structure, the reduced gland density [22] and the brosis and atrophy of the endometrium [8] of aged hens probably caused by sustained laying behavior would contribute to the uterine hypofunction of protein synthesis, ion transport and immune defense. However, a comprehensive understanding of uterine functional differences in terms of eggshell biomineralization between young and aged hens at the transcriptome level remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Eggshell in the late phase of production possessed lower breaking strength, accompanied with a greater variability in structural properties such as thickness, grain morphology and crystal texture [7]. Besides, the percentages of abnormal structure such as type B mammillae and late fusion in eggshell from aged hens were higher than those from young hens [8], which was thought to contribute to the impairment of mechanical properties. Therefore, age-related abnormalities in ultrastructure could be one reasonable explanation for the compromised shell quality in the late laying period.…”
Section: Introductionmentioning
confidence: 99%
“…Age-related changes in the expression of matrix proteins (ovalbumin, ovotransferrin and ovocleidin-17) in uterus of laying hens were suggested by their varying concentration in eggshell [20,21]. Besides, a destructed uterine structure, the reduced gland density [22] and the brosis and atrophy of the endometrium [8] of aged hens probably caused by sustained laying behavior would contribute to the uterine hypofunction of protein synthesis, ion transport and immune defense. However, a comprehensive understanding of uterine functional differences in terms of eggshell formation between young and aged hens at the transcriptome level remains obscure.…”
Section: Introductionmentioning
confidence: 99%